2023
DOI: 10.3390/agronomy13112673
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to Stimulate Morpho-Physio-Biochemical Traits of Maize for Efficient Production under Drought Stress in Tropics Field

Md. Samim Hossain Molla,
Orawan Kumdee,
Nattaporn Worathongchai
et al.

Abstract: Maize, a major food source for the world’s tropical regions, is often impaired by droughts under a changing climate, which creates the importance of making efforts to improve the tolerance characteristics of maize under field conditions. The experiment was conducted during the dry season of the 2020–2021 period to investigate the stimulatory effects of plant growth regulator (PGR) ethephon (2-chloroethylphosphonic acid) on the morpho-physio-biochemical traits of maize and to identify suitable application appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…This might be because ethephon helps break down starch [ 111 ] into sugars that are soluble. Applying ethephon reduced the electrolyte leakage of maize leaves during drought stress [ 74 ]. Ethephon can improve cell membrane integrity by promoting the synthesis of specific proteins and enzymes that aid in shielding the membranes from harm [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because ethephon helps break down starch [ 111 ] into sugars that are soluble. Applying ethephon reduced the electrolyte leakage of maize leaves during drought stress [ 74 ]. Ethephon can improve cell membrane integrity by promoting the synthesis of specific proteins and enzymes that aid in shielding the membranes from harm [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extreme rainfall in a certain short period, especially during the later growth stage, i.e., kernel filling stage of maize, may increase the lodging percentage of maize plant and can significantly hamper kernel growth and ultimately kernel yield [ 54 , 55 , 69 ]. Scientists found that ethephon enhances stem strength by increasing stem dry matter concentration and stem width and reducing plant height and leaf area, which helps plants stand against lodging [ 54 , 55 , 69 , 70 , 71 , 72 , 73 , 74 ]. However, it is imperative to investigate the effectiveness of ethephon for maize production under rainfed conditions, and in this regard, stress tolerance indices may be helpful methods for identifying the stress tolerance potential of crop genotypes or technologies [ 35 ].…”
Section: Introductionmentioning
confidence: 99%